Types of Evidence in Criminal Trials: Questions Relationships - P. V. Kozlowski (Сибирское юридическое обозрение, 2011)
In this paper, we propose to divide proof into 3 conventional groups, as well as the ratio of evidence provided in each of the groups proposed by the author.